Peran dan Kedudukan Kalang dalam Pemerintahan Masa Kerajaan Mataram Kuno Berdasarkan Data Prasasti - Yasmin Nindya Chaerunissa (Penerbit BRIN (BRIN Publishing), 2025)
Abstract. The Role and Status of the Kalang in the Administration of the Ancient Mataram Kingdom Based on Epigraphic Data. Kalang was an officer at the wanua (village) level and frequently mentioned in various inscriptions, especially regarding sīma ceremonies. The position of Kalang is associated with people whose work was related to forests and timber. Although there have been several previous studies on Kalang, discussions on the role and position of Kalang in the village administration during the Mataram Kingdom based on the details of pasĕk-pasĕk (gift) they received in ceremonies are still limited. This research aims to analyse the role and position of Kalang in the government during the Mataram Kingdom based on inscriptional data. This research uses a qualitative approach by collecting data from 29 inscriptions from 804 CE to 909 CE. The data was then subjected to processing, content analysis, and interpretation. The results of this study show that Kalang did not only stand as Kalang alone, but there were also other positions related to Kalang such as Tuha Kalang, Kalang Manguwu, Kalang Tunggu Durung, and others, which signalled the difference in their roles from one another. As for status, the results show that in some villages during the late Rakai Kayuwangi period and briefly during the Dyah Balitung period, Kalang and other Kalang-related positions occupied a high degree within the wanua bureaucracy, as seen from the number of pasĕk-pasĕk received which tended to be higher than other officials from the village that organised the ceremony. Keywords: Kalang, Mataram Kingdom, Inscriptions, Pasĕk-Pasĕk Abstrak. Kalang adalah jabatan di tingkat wanua (desa) dan kerap disebut dalam berbagai prasasti, utamanya mengenai upacara penetapan sīma. Posisi Kalang erat diasosiasikan dengan orang-orang yang pekerjaannya berkaitan dengan hutan dan kayu. Meski telah ada beberapa penelitian terdahulu mengenai Kalang, pembahasan mengenai peran dan kedudukan Kalang dalam bidang pemerintahan desa masa Kerajaan Mataram Kuno secara spesifik, misalnya melihat secara detail pasĕk-pasĕk (semacam hadiah) yang mereka terima dalam upacara, masihlah terbatas. Penelitian ini bertujuan untuk menganalisis peran dan kedudukan Kalang dalam pemerintahan pada masa Kerajaan Mataram Kuno berdasarkan data prasasti. Riset ini menggunakan pendekatan kualitatif dengan mengumpulkan data dari 29 prasasti yang berasal dari tahun 804 M hingga 909 M. Data tersebut kemudian dilakukan pengolahan, analisis isi, dan interpretasi. Hasil penelitian ini menunjukkan bahwa Kalang tidak hanya berdiri sebagai Kalang saja, namun juga ada jabatan lain terkait Kalang seperti Tuha Kalang, Kalang Manguwu, Kalang Tunggu Durung, dan lain-lain, yang menandakan perbedaan peran mereka satu sama lain. Sementara perihal kedudukan, hasil menunjukkan bahwa di beberapa desa pada masa akhir Rakai Kayuwangi dan sempat pada masa Dyah Balitung, Kalang dan jabatan lain terkait Kalang menempati derajat yang tinggi dalam birokrasi di wanua, sebagaimana dilihat dari jumlah pasĕk-pasĕk yang diterima cenderung lebih tinggi dibanding pejabat lain dari desa penyelenggara upacara. Kata kunci: Kalang, Kerajaan Mataram Kuno, Prasasti, Pasĕk-Pasĕk